Effectiveness Implementation Law Protection Consumers : Case Study of Consumer Disputes in Indonesia - Elisabeth Saragih; Yasmirah Mandasari Saragih; MH Fauzan; Lasma Sinambela; Kaaisar Romolus Deo Sianipar (International Journal of Law, Crime and Justice, 2024)
This study aims to analyze the effectiveness of consumer protection law implementation in Indonesia, particularly through a case study approach on disputes between consumers and business actors. The research employs a qualitative method with normative and empirical juridical approaches. Data were obtained from legal documents, case reports, and interviews with relevant stakeholders. The findings reveal that although consumer protection regulations are comprehensive, their implementation faces challenges, such as low public legal awareness, weak law enforcement, and insufficient support from consumer protection institutions. This study recommend strengthening legal education, increasing the capacity of relevant institutions, and simplifying dispute resolution mechanisms.